The product liability system in China: recent changes and prospects - Thomas, Kristie (Cambridge University Press, 2014)
Following the enactment of the 2009 Tort Liability Law, the product liability system in China is largely complete. This article sketches the development of this system before outlining some of the main substantive provisions in force today and drawing comparisons between the Chinese approach and the US and European provisions. The Article will conclude that China’s product liability system provides an interesting case study which enriches the study of global trends and norms in the product liability arena. In line with many other countries, particularly in the Asia-Pacific region, the main influence on China has been the EC Directive rather than the US model.